2007
DOI: 10.1119/1.2768690
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Forces Between Magnetic Dipoles

Abstract: We describe a simple undergraduate lab in which students determine how the force between two magnetic dipoles depends on their separation. We consider the case where both dipoles are permanent and the case where one of the dipoles is induced by the field of the other (permanent) dipole. Agreement with theoretically expected results is quite good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…They have validated their model for the case in which the surfaces of the two particles are in contact with each other. Recently, Castaner et al [8], Gayetsky and Caylor [9], Kraftmakher [10] and PintoEspinoza [11] have further investigated the dipole-dipole interaction in a uniform magnetic field.…”
mentioning
confidence: 99%
“…They have validated their model for the case in which the surfaces of the two particles are in contact with each other. Recently, Castaner et al [8], Gayetsky and Caylor [9], Kraftmakher [10] and PintoEspinoza [11] have further investigated the dipole-dipole interaction in a uniform magnetic field.…”
mentioning
confidence: 99%
“…There are several studies in which approximate solutions of (1) were obtained. In these studies, it was shown that the magnetic field is proportional to the power law of distance as z −3 and the magnetic force is proportional to z −4 when a ≫ z [12,13]. Also, there are several articles where both the field and the force between the two magnets are examined theoretically by using relatively complex mathematical solutions [12,14].…”
Section: Theoretical Analysismentioning
confidence: 99%
“…All the terms independent of the displacement ∆z is considered as a constant C in (13). It was found from force expression (6) that ∆z is an approximate linear function of sin α .…”
Section: Measurement Linear Fit 3th Degree Polynomial Fitmentioning
confidence: 99%
“…It should be remarked that the result of this investigation depends quite heavily on the type of magnets used and the geometry. For instance, short 'squat' magnets with larger area of the poles and shorter distance between the poles gives a relationship of the above form but with n of about 3-4 (Gayetsky and Caylor 2007).…”
Section: The Force Between Two Bar Magnetsmentioning
confidence: 99%